Comparison of Lymphedema Incidence Between 2 Lymphadenectomy Techniques in Patients With Uterine Cancer Undergoing Robotic Staging. Issue 1 (1st January 2015) - Menderes, Gulden; Azodi, Masoud; Schwartz, Peter; Silasi, Dan-Arin
Abstract : Objective: This study aimed to compare the incidence of lower extremity lymphedema in patients with uterine cancer after robotic staging using the following 2 methods: standard and selective pelvic lymphadenectomy. Materials and Methods: Three hundred forty-four consecutive patients who presented with endometrial cancer from March 2007 to October 2012 underwent robotic staging. Surgeon A performed standard pelvic lymphadenectomy and surgeon B performed selective lymphadenectomy. Selective pelvic lymphadenectomy spared the lateral chain of the external iliac lymph nodes (LNs). The incidence of lymphedema and staging adequacy between the 2 groups were analyzed. Results: Standard pelvic lymphadenectomy was performed in 238/344 (69.2%) patients and selective pelvic lymphadenectomy was performed in 106/344 (30.8%) patients. Conversion to laparotomy occurred in 2/344 cases (0.6%). Mean age for 344 patients was 63.6 (10) years and body mass index was 34.8 (10.1) kg/m 2 . The mean operative time was 162.3 (54.6) minutes. Postoperative hospitalization was 1.62 (1.93) days. Histology included 80.8% endometrioid adenocarcinomas and 19.2% clear cell, serous, and carcinosarcomas. Mean pelvic LN counts for the standard and selective pelvic lymphadenectomy groups were 16 (8.6) and 15.5 (7.1), respectively ( P = 0.31). Mean numbers of para-aortic LNs retrieved for the standard and selective lymphadenectomy groups were 3.1 (4.1) and 4.9 (4.5), respectively ( P < 0.01). Median follow-up was 29.3 months (interquartile range, 15.6–43.1 months). The difference in the incidence of lower extremity lymphedema was statistically significant: 4.6% (11/238 patients) in the standard lymphadenectomy group versus 0.9% (1/106 patients) in the selective lymphadenectomy group ( P = 0.03). Conclusions: When compared to the standard technique, selective pelvic lymphadenectomy with sparing of the lateral chain of the external iliac LNs is adequate and results in a lower incidence of lower extremity lymphedema.